The effect of supplements of crop residues and agro-industrial by-products on the growth performance of Swazi goats - Ogwang, B.H.; Karua, S.K. (International Livestock Research Institute, 1996)
Goat production in Swaziland is characterized by low offtake resulting from lack of management of rangelands and seasonal fluctuations in feed resources. Periodic droughts and extensive dry spells in winter which cause nutritional stress result in low productivity of the goats. The aim of the study reported here was to assess the growth response in young male Swazi goats grazed on natural pastures to supplementation with maize stover, sugar-cane tops and dry pineapple pulp. The major findings from the study were that (a) the growth rates in goats under natural grazing can be improved by protein supplementation (b) dried pineapple pulp has considerable potential as an energy feed for goats (c) higher growth rates can be achieved by supplementing the pineapple pulp with protein (d) maize stover and sugar-cane tops, in their present form, have limited possibility for improving weight gains in goats.